Antiplatelet Effect of Differentially Charged Pegylated Lipid-Polymer Nanoparticles - Vilos-Ortiz, C (Elsevier Inc., 2017)
PEGylated nanoparticles have been extensively investigated in different platforms for drug delivery. However, the physiological effects related to platelet activation, and the potential procoagulant activity which could lead to thrombosis and further cardiovascular diseases have not been widely examined. In this work, we studied the effect of differentially charged PEGylated lipid-polymer nanoparticles in the human platelet aggregation and activation by light transmission aggregometry and flow cytometry. PEGylated nanoparticles inhibited the platelet aggregation with a dose dependency (350, 700, and 1400 μg/mL) in both ADP- and collagen-induced platelet aggregation, and P-selectin expression. Charged nanoparticles (anionic and cationic) presented higher inhibitions of the platelet aggregation compared to neutral nanoparticles, and particularly the cationic particles generated a slightly higher effect. The obtained results demonstrated the safety of the differentially charged PEGylated lipid-polymer nanoparticles, and their ability to inhibit the aggregation and activation of human platelets stimulated by two classic platelet activators. © 2016 Elsevier Inc.